A cross‐taxa assessment of pelagic longline by‐catch mitigation measures: conflicts and mutual benefits to elasmobranchs. Issue 3 (20th January 2016) - Gilman, Eric; Chaloupka, Milani; Swimmer, Yonat; Piovano, Susanna
Abstract: Elasmobranch mortality in pelagic longline fisheries poses a risk to some populations, alters the distribution of abundance between sympatric competitors, changing ecosystem structure, processes and stability. Individual and synergistic effects on elasmobranch catch and survival from pelagic longline gear factors, including methods prescribed to mitigate bycatch of other vulnerable taxa, were determined. Overall relative risk of higher circle vs. J‐shaped hook shark catch rates conditioned on potentially informative moderators, from 30 studies, was estimated using an inverse‐precision weighted mixed‐effects meta‐regression modelling approach. Sharks had a 1.20 times (95% CI: 1.03–1.39) significantly higher pooled relative risk of capture on circle hooks, with two significant moderators. The pooled relative risk estimate of ray circle hook catch from 15 studies was not significant (RR = 1.22, 95% CI: 0.89–1.66) with no significant moderators. From a literature review, wire leaders had higher shark catch and haulback mortality than monofilament. Interacting effects of hook, bait and leader affect shark catch rates: hook shape and width and bait type determine hooking position and ability to sever monofilament leaders. Circle hooks increased elasmobranch catch, but reduced haulback mortality and deep hooking relative to J‐shaped hooks of the same or narrower width. Using fish vs. squid for bait increased shark catch and deep hooking. Pelagic stingray ( Pteroplatytrygon violacea ) catch and mortality were lower on wider hooks. Using circle instead of J‐shaped hooks and fish instead of squid for bait, while benefitting sea turtles, odontocetes and possibly seabirds, exacerbates elasmobranch catch and injury, therefore warranting fishery‐specific assessments to determine relative risks.